The Future Research Opportunity of Community-Based Tourism - Purnomo, Agustina (Politeknik Pariwisata NHI Bandung, 2025)
Community-based tourism aims to counteract tourism development with the well-being of local communities. There has been extensive research on this topic, but more input is needed for researchers to understand future research opportunities. This study used bibliometric analysis to analyze a large dataset of 70,911 articles from ScienceDirect. The researcher utilized VosViewer to process the data and identify recommendations for future research topics in community-based tourism. The analysis revealed potential research topics, developments in these topics, and areas with potential for novel exploration. These findings represent valuable future research opportunities in community-based tourism that warrant further investigation.